Environmental drivers and the distribution of cold-water corals in the global ocean - Tong, Ruiju; Davies, Andrew J.; Yesson, Chris; Yu, Jinsongdi; Luo, Yuan; Zhang, Ling; Burgos, Julian M. (Frontiers in Marine Science, 2023)
Species distribution models (SDMs) are useful tools for identifying the distribution of marine species in data limited environments. Outputs from SDMs have been used to identify areas for spatial management, analyzing trawl closures, quantitatively measuring the risk of bottom trawling, and evaluating protected areas for improving conservation management. Cold-water corals are globally distributed habitat forming organisms that are vulnerable to anthropogenic impacts and climate change, but data deficiency remains an ongoing issue for the effective spatial management of these important ecosystem engineers. In this study, we constructed 11 environmental seabed variables at 500m resolution based on the latest multi-depth global datasets and high-resolution bathymetry. Ensemble modeling methods wasere used to predict the global habitat suitability for ten widespread cold-water coral species, including six reef Scleractinian framework-forming species and four large gorgonian species. Depth, terrain ruggedness index, salinity, tTemperature, depth, salinity, terrain ruggedness index, carbonate saturation stateomega calcite and current velocitychlorophyll were the most important factors in determining the global distributions of these species. The Scleractinian framework forming species Madrepora oculata showed the widest niche breadth, whilst most other species demonstrated somewhat limited niche breadthoverlap. The shallowest study species, Oculina varicosa, had the most distinctive niche of the group. The model outputs from this study represent the highest resolution global predictions for these species to date and are valuable in aiding the management, conservation and continued research into cold-water coral species.